Kepemimpinan Laki- Laki dan Perempuan dalam Islam - Anshori Anshori (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2006)
The leadership question of male and female in Islam often becomes controversial. it could not happened when Muslims understand the text of Al-Qur'an and Hadis comprehensively, Husband can be a leader in his family becuse of his responsibilty in searching family needs (life cost). The leadership in society is not dtermined by gender or sex but byquality.